The handbook of language variation and change - Chambers, J. K.; Schilling-Estes, Natalie ([Hoboken] : Wiley-Blackwell, is an imprint of John Wiley, 2013)
Reflecting a multitude of developments in the study of language change and variation over the last ten years, this extensively updated second edition features a number of new chapters and remains the authoritative reference volume on a core research area in linguistics. A fully revised and expanded edition of this acclaimed reference work, which has established its reputation based on its unrivalled scope and depth of analysis in this interdisciplinary field includes seven new chapters, while the remainder have undergone thorough revision and updating to incorporate the latest research and reflect numerous developments in the field.
Part I. Data collection -- part II. Evaluation -- part III. Linguistic structure -- part Ivolume Language and time -- part volume Social differentiation -- part VI. Domains -- part VII. Contact -- part VIII. Sociolinguistics and their communities.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Language and languages -- Variation; Linguistic change; FOREIGN LANGUAGE STUDY -- Ancient Languages; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative; Language and languages -- Variation; Linguistic change; Sprachwandel; Sprachvariante; Electronic books; Electronic books